Regulatory T Cells in Allergic Asthma - Mubasher, Mobeen (The Meducator, 2018)
T regulatory cells (Tregs) are a subset of T cell leukocytes that play a key role in modulating the immune system, maintaining tolerance to self-antigens and suppressing excessive immune responses that go on to harm the host. Much like T helper (Th) cells, Tregs belong to a broader class of CD4+ T cells that develop from pluripotent hematopoietic stems cells in the bone marrow and mature in the thymus. Within the context of allergic asthma, Tregs are central to the process of pulmonary regulation by continuously combatting both immunogenic and harmless antigens. By releasing cytokines such as IL-10 and TGF-ß, Tregs modulate the inflammatory Th2-type immune response which, when dysregulated can drive asthma development as well as the hallmark asthmatic signs- airway hyperresponsiveness, bronchoconstriction, and gland hyperplasia/hypersecretion. This review will explore the function of Tregs as well as their modulatory role within allergic asthma.